2013
DOI: 10.1021/ma400061a
|View full text |Cite
|
Sign up to set email alerts
|

Precursor of Shish-Kebab above the Melting Temperature by Microbeam X-ray Scattering

Abstract: Preparation of strong fiber with ultrahigh strength and modus is a dream of polymer scientists and engineers. It is believed that a shish-kebab is the structure origin of the ultrahigh strength and modulus fiber. This article presents our investigation on the inner structure of shish-kebab precursor of isotactic polystyrene in μm scale formed by shear flow above the nominal melting temperature T m using microbeam wide-and small-angle X-ray scattering (WAXS and SAXS). The microbeam WAXS experiments indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 28 publications
1
70
0
Order By: Relevance
“…The experiment result suggests the formation of flow-induced noncrystalline precursors. With SR-μSXRD, Kanaya et al 64 showed that shear-induced precursors contained limited crystallinity with higher thermal stability than normal lamellar crystals. The above two SR-μSXRD studies seem reaching contrary conclusion on the structure of precursors, which may be due to their different experimental procedures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The experiment result suggests the formation of flow-induced noncrystalline precursors. With SR-μSXRD, Kanaya et al 64 showed that shear-induced precursors contained limited crystallinity with higher thermal stability than normal lamellar crystals. The above two SR-μSXRD studies seem reaching contrary conclusion on the structure of precursors, which may be due to their different experimental procedures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The route to crystallization during flow is generally accepted to be via the formation of 'shishkebab' morphology [6][7][8][9]. Proposed mechanisms and kinetics for the formation of shish-kebab morphology usually relate to data from shear flow conditions using custom made shearing devices [10][11][12][13][14][15][16]. However, during extrusion, the polymer melt exits the die head and begins to cool rapidly, and at the same time it is uniaxially elongated under constant force, between the die head and take-up device.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in shear‐induced crystallization (SIC) have demonstrated the existence of three regimes which, for the same polymer at the same temperature and pressure, occur on increasing the flow intensity: (i) the effect of flow upon the final morphologies and crystallization kinetics is negligible, (ii) the flow causes a strong enhancement of crystallization kinetics, increasing the number of nuclei and thus the average dimension decreases, but the spherulitic morphology is kept, (iii) the flow deeply influences both morphology and kinetics by causing the formation of fibrillar structures in the polymer melt. However, apart from a qualitative understanding of the phenomena, a quantitative description of the phenomena is still discussed and it is currently under investigation …”
Section: Introductionmentioning
confidence: 99%